Acute effects of a caffeine-taurine energy drink on repeated sprint performance of American college football players - Gwacham, N.; Wagner, D. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
Consumption of energy drinks is common among athletes; however, there is a lack of research on the efficacy of these beverages for short-duration, intense exercise. The purpose of this research was to investigate the acute effects of a low-calorie caffeine-taurine energy drink (AdvoCare Spark) on repeated sprint performance and anaerobic power in National Collegiate Athletic Association Division I football players. Twenty football players (age 19.7 ± 1.8 yr, height 184.9 ± 5.3 cm, weight 100.3± 21.7 kg) participated in a double-blind, randomized crossover study in which they received the energy drink or an isoenergetic, isovolumetric, noncaffeinated placebo in 2 trials separated by 7 days. The Running Based Anaerobic Sprint Test, consisting of six 35-m sprints with 10 s of rest between sprints, was used to assess anaerobic power. Sprint times were recorded with an automatic electronic timer. The beverage treatment did not significantly affect power (F = 3.84, p = .066) or sprint time (F = 3.06, p = .097). However, there was a significant interaction effect between caffeine use and the beverage for sprint times (F = 4.62, p = .045), as well as for anaerobic power (F = 5.40, p = .032), indicating a confounding effect. In conclusion, a caffeine-taurine energy drink did not improve the sprint performance or anaerobic power of college football players, but the level of caffeine use by the athletes likely influenced the effect of the drink.